Molecular light-upconversion: we have had a problem! When excited state absorption (ESA) overcomes energy transfer upconversion (ETU) in Cr(iii)/Er(iii) complexes. Issue 23 (30th April 2021) - Golesorkhi, Bahman; Taarit, Inès; Bolvin, Hélène; Nozary, Homayoun; Jiménez, Juan-Ramón; Besnard, Céline; Guénée, Laure; Fürstenberg, Alexandre; Piguet, Claude
Abstract : Near-infrared to visible molecular upconversion exhibits quantum yields which are 2–6 orders of magnitude larger than those modeled with the accepted linear excited state absorption (ESA) or energy transfer (ETU) mechanisms: we have had a problem! Abstract : Nine-coordinate [ErN9 ] or [ErN3 O6 ] chromophores found in triple helical [Er(L )3 ] 3+ complexes (L corresponds to 2, 2′, 6′, 2′′-terpyridine (tpy), 2, 6-(bisbenzimidazol-2-yl)pyridine (bzimpy), 2, 6-diethylcarboxypyridine (dpa-ester) or 2, 6-diethylcarboxamidopyridine (dpa-diamide) derivatives), [Er(dpa)3 ] 3− (dpa is the 2, 6-dipicolinate dianion) and [GaErGa(bpb-bzimpy)3 ] 9+ (bpb-bzimpy is 2, 6-bis((pyridin-2-benzimidazol-5-yl)methyl-(benzimidazol-2-yl))pyridine) exhibit NIR (excitation at 801 nm) into visible (emission at 542 nm) linear light upconversion processes in acetonitrile at room temperature. The associated quantum yields 5.5(6) × 10 −11 ≤ ϕ uptot(ESA) ≤ 1.7(2) × 10 −9 appear to be 1–3 orders of magnitude larger than those predicted by the accepted single-center excited-state absorption mechanism (ESA). Switching to the alternative energy transfer upconversion mechanism (ETU), which operates in multi-centers [CrErCr(bpb-bzimpy)3 ] 9+, leads to an improved quantum yield of ϕ uptot(ETU) = 5.8(6) × 10 −8, but also to an even larger discrepancy by 4–6 orders of magnitude when compared with theoretical models. All photophysical studies point to Er( 4 I13/2 ) as being the only available 'long-lived' (1.8 ≤ τ ≤ 6.3 μs) and emissive excited state, which works as an intermediate relay for absorbing the second photon, but with an unexpected large cross-section for an intrashell 4f → 4f electronic transition. With this in mind, the ETU mechanism, thought to optimize upconversion via intermetallic Cr → Er communication in [CrErCr(bpb-bzimpy)3 ] 9+, is indeed not crucial and the boosted associated upconversion quantum yield is indebted to the dominant contribution of the single-center erbium ESA process. This curious phenomenon is responsible for the successful implementation of light upconversion in molecular coordination complexes under reasonable light power intensities, which paves the way for applications in medicine and biology. Its origin could be linked with the presence of metal–ligand bonding.